Radical Rag: The Pioneer Labour Press in Canada - Verzuh, Ron (Steel Rail, 1988)
Canada's trade unions have long claimed a prominent place in the struggle for social democracy. From the earliest years of that struggle, the labour movement's press has been on the front lines. Radical Rag tells the colourful story of those pioneer days, recounting the war for social justice fiercely waged through the pages of labour's weekly newspapers.... –Publisher's description on book cover
OCLC: 27036817
Keywords: 1800-1899; Arbeiterpresse; Canada; History; Kanada; Labor movement; Labor movement Canada History 19th century; Mouvement ouvrier Canada Histoire 19e siècle; Press; Labor; Press; Labor Canada History 19th century; Presse ouvrière Canada Histoire 19e siècle; Travailleurs Canada Histoire 19e siècle; Working class; Working class Canada History 19th century